Association Between Family Support and Post-Stroke Activity of Daily Living Autonomy - Esa Karunia (Universitas Airlangga, 2016)
The number of stroke patients in Indonesia has increased every year. Stroke has several impacts, namely disability that can affect or interfere with someone in conducting Activity of Daily Living (ADL). Stroke can also cause depression, so family support is needed so that stroke patients can do activities. This study aims to analyze the relationship between family support and independence in conducting ADL post-stroke. This study was an analytic observational study, with a research design that is a cross-sectional design. The sampling method uses simple random sampling with 47 respondents. The study was conducted at the Medical Rehabilitation Installation of the Haji Public Hospital, Surabaya in June-July 2015. The independent variables in this study were age, sex, work, and family support, while the dependent variable was ADL independence after stroke. The results of the study mentioned that the majority of post-stroke respondents were 43-61 years old, were male, and did not work. Most respondents get good family support so that respondents can be more independent in their activities. Based on the analysis using Chi-square, there is a relationship between family support and independence in performing ADL post-stroke, p-value = 0.018 with α = 0.05), but there is no relationship between age, sex, and occupation with ADL post-stroke independence. It is expected that the family creates a calm situation, as well as creating activities that are useful for the independence of people after stroke.